A first-principles study of the properties of four predicted novel phases of AlN. (May 2017) - Yang, Ruike; Zhu, Chuanshuai; Wei, Qun; Du, Zheng
Abstract: Structural, elastic, thermodynamic, electronic and optical properties of four predicted novel AlN phases ( Pmn2 1 -AlN, Pbam -AlN, Pbca -AlN and Cmcm -AlN) are calculated using first-principles according to density function theory (DFT). These phases were found using the CALYPSO method but have not yet been synthesized experimentally. Here we predict some of their properties. The properties are analyzed by means of GGA-PBE and PBE0 respectively. The more precision results are obtained by PBE0. Cmcm -AlN owns better plasticity and it's Young's modulus has clearer anisotropy than Pmn2 1 -AlN, Pbam -AlN and Pbca -AlN. The Debye temperature, under higher temperature, shows weak temperature dependence and approach to a constant value. The Dulong-Petit limit of all four novel AlN phases and wz -AlN is about 48 J mol −1  K −1 and they have almost the same temperature law. The band structures show that the four AlN are the wide direct band gap semiconductors, which band gaps are 5.95 ( Pmn2 1 -AlN), 5.99 ( Pbam -AlN), 5.88 ( Pbca -AlN) and 5.59 eV ( Cmcm -AlN). The bonding behaviors are the combination of covalent and ionic nature. The dielectric constants, refractive index, reflectivity, absorption, loss spectra, conductivity and Raman spectra are also calculated in detail. All four phases have a lower plasma frequency than of wz-AlN. Highlights: Four AlN are wide direct band gap semiconductors (gaps are 5.95, 5.99, 5.88 and 5.59 eV). Structural stability factors of the four phases are the interaction between N p and Al p. The Dulong-Petit limit of all four novel phases is about 48 J mol −1  K −1 . All four phases have a lower plasma frequency than of wz -AlN.